2020
DOI: 10.3390/ijerph17030752
|View full text |Cite
|
Sign up to set email alerts
|

Gamified M-Health Attention Bias Modification Intervention for Individuals with Opioid Use Disorder: Protocol for a Pilot Randomised Study

Abstract: Introduction: Globally, there is an epidemic of opioid use disorders. Locally, in Singapore, there is an increase in the number of individuals abusing opioids. The advances in experimental psychology have highlighted the need to modify unconscious, automatic biases. These automatic, unconscious biases result in individuals having preferential attention to substance-related cues in their natural environment, thus leading to a slip or relapse back into their underlying addictive disorders. Prior studies have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Whilst Zhang et al (2019)'s [18] prior work was aimed at determining the feasibility and acceptability of the mobile intervention, they found that 14 out of their 30 participants had a change in their baseline biases. Zhang et al (2020) [19] have recently also described a protocol, that examines if a co-designed gamified attention bias modification intervention was more effective as compared to the conventional intervention. Unfortunately, the authors have not shared any further results.…”
Section: Technological Advances and Its Impact On Bias Modificationmentioning
confidence: 99%
“…Whilst Zhang et al (2019)'s [18] prior work was aimed at determining the feasibility and acceptability of the mobile intervention, they found that 14 out of their 30 participants had a change in their baseline biases. Zhang et al (2020) [19] have recently also described a protocol, that examines if a co-designed gamified attention bias modification intervention was more effective as compared to the conventional intervention. Unfortunately, the authors have not shared any further results.…”
Section: Technological Advances and Its Impact On Bias Modificationmentioning
confidence: 99%